Tissue immunostaining for factor XIIIa in dermal dendrocytes of pityriasis alba skin lesions - Francisca Regina Oliveira Carneiro; Gabriela Borborema do Amaral; Maiana Darwich Mendes; Juarez Antônio Simões Quaresma (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND: Pityriasis alba affects 1% of the world population and about 9.9% of the children in Brazil. However, its etiology remains uncertain. OBJECTIVE: The objective of the present study was to evaluate the immunoexpression of factor XIIIa in dermal dendrocytes of skin lesions of pityriasis alba. METHOD: Twenty patients with pityriasis alba and 20 patients with atopic dermatitis underwent biopsy. The dermal dendrocytes marked by factor XIIIa were counted by means of immunohistochemical analysis. RESULTS: The mean amount of dermal dendrocytes found in the patients with pityriasis alba was 2, whereas in the patients with atopic dermatitis it was 4, with a statistically significant difference between them. A cutoff point of 3 cells/square inch was established to differentiate pityriasis alba from atopic dermatitis, with 80% sensibility and 90% specificity. CONCLUSION: We believe that pityriasis alba and atopic dermatitis should be considered different clinical forms within the spectrum of atopic disease, in which sun radiation plays an important role by modulating the progression of the disease.